Biochar improves the morphological, physiological and biochemical properties of white willow seedlings in heavy metal-contaminated soil - Mokaram-Kashtiban, Sahar; Hosseini, Seyed Mohsen; Tabari Kouchaksaraei, Masoud; Younesi, Habibollah (Archives of Biological Sciences, 2019)
Paper description: Biochar is a multipurpose soil amendment that improves plant growth, microbial activity, water and nutrient retention capacity, and ameliorates heavy metal phytotoxicity. White willow, as a metal accumulator plant, has showed different responses to pinewood biochar amendment in heavy metal-contaminated soils. There is a need for further studies to determine the effect of biochar on this plant. This study presents the effects of broadleaf wood biochar on white willow seedlings grown in clean and soils contaminated with heavy metals, and investigated their morphological, biochemical and physiological responses. Abstract: Biochar is an efficient soil amendment used for promoting plant resistance to heavy metal (HM)-contaminated soils. There is a need for further investigation of its impacts on plants and soil. This study was undertaken as a pot experiment to assess the effect of biochar (0, 2.5, and 5% mass fractions) on the morphological, physiological and biochemical responses of white willow seedlings (Salix alba L.) cultured in uncontaminated soil and mixed soil contaminated with HM (Cu, Pb, and Cd). Additionally, some chemical properties and HM bioavailability were evaluated. Biochar increased height and diameter, root elongation, leaf area and dry biomass of the seedlings in both soils. Its addition to the contaminated soil reduced electrolyte leakage, the malondialdehyde and proline contents but increased the chlorophyll content, net photosynthesis rate, intercellular CO2 concentration and transpiration rate in the leaf. Use of biochar (especially at 5% rate) in both soils, increased soil pH, total nitrogen, soil organic carbon and available P and K, while in the contaminated soil the availability of Cu, Pb, and Cd decreased. The results showed that biochar is a suitable amendment to contaminated soils that improves plant properties by improving soil chemical features and immobilizing HMs. https://doi.org/10.2298/ABS180918010M Received: September 18, 2018; Revised: February 9, 2019; Accepted: February 14, 2019; Published online: March 1, 2019 How to cite this article: Mokarram-Kashtiban S, Hosseini SM, Kouchaksaraei Masoud Tabari, Younesi H. Biochar improves the morphological, physiological and biochemical properties of white willow seedlings in heavy metal-contaminated soil. Arch Biol Sci. 2019;71(2):281-91.